2023
DOI: 10.1136/bmjresp-2022-001585
|View full text |Cite
|
Sign up to set email alerts
|

Use and persistence of single and multiple inhaler triple therapy prescribed for patients with COPD in France: a retrospective study on THIN database (OPTI study)

Gaétan Deslee,
Caroline Fabry-Vendrand,
Nolwenn Poccardi
et al.

Abstract: IntroductionFrom 2018 single inhaler triple therapy (SITT) became available in France to treat moderate-to-severe chronic obstructive pulmonary disease (COPD). Given its simplified inhaler use compared with multiple inhaler triple therapy (MITT), this therapeutic option has the potential to offer benefit in terms of improved persistence and adherence. Given the lack of real-world evidence of the effectiveness of triple therapy, this study was designed to evaluate the use of MITT and SITT in France and compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Few studies have compared different ICSs and a range of doses comparing both efficacy and safety endpoints in COPD subjects. In the ETHOS study, a reduction in mortality was only observed with the SITT containing budesonide at a dose of 400 mcg, but not at 200 mcg twice daily [8]. However, both ICS dosages assured the same reduction in exacerbation rate (a key driver in achieving improved survival) with respect to the LABA/LAMA.…”
Section: Ics Mechanism Of Action Comparison Between Molecules and Pro...mentioning
confidence: 97%
See 1 more Smart Citation
“…Few studies have compared different ICSs and a range of doses comparing both efficacy and safety endpoints in COPD subjects. In the ETHOS study, a reduction in mortality was only observed with the SITT containing budesonide at a dose of 400 mcg, but not at 200 mcg twice daily [8]. However, both ICS dosages assured the same reduction in exacerbation rate (a key driver in achieving improved survival) with respect to the LABA/LAMA.…”
Section: Ics Mechanism Of Action Comparison Between Molecules and Pro...mentioning
confidence: 97%
“…The INvestigation of TRelegy Effectiveness: usual PractIce Design (INTREPID) study showed that the use of SITT improved health status, as evaluated by the COPD Assessment Test (CAT), more than the MITT [5]. Other retrospective or prospective studies including pharmacy data suggest that the use of SITT may improve adherence, persistence, and, sometimes, symptoms and exacerbations compared with MITT [6][7][8].…”
Section: History Of Ics Use In Copd Subjectsmentioning
confidence: 99%